Pulmonary Sarcomatoid Carcinoma Associated with Arterial Thromboembolism in a Cat - Aria L. Guarino; Albert B. Jeon; Jeffrey R. Abbott; Richard C. Hill (Case Reports in Veterinary Medicine)
A 14-year-old, neutered male domestic shorthair cat presented for acute monoparesis with physical exam findings and biochemical data supportive of a distal arterial thromboembolism. Thoracic radiographs revealed an alveolar pattern in the right middle lung lobe and multifocal nodules in other lung lobes. A pulmonary mass was found on necropsy, which was composed of both carcinomatous and sarcomatous components, confirmed with cytokeratin and vimentin immunohistochemistry. Using the World Health Organization classification scheme for mixed pulmonary tumors, this tumor would be characterized as a pleomorphic squamous cell carcinoma under the umbrella term of pulmonary sarcomatoid carcinoma. The World Health Organization classification of mixed pulmonary tumors and its application to previously reported mixed pulmonary tumors in companion animals is discussed. This is the first reported case of this tumor type in a cat, as well as the first report of this tumor type associated with an arterial thromboembolism in any veterinary species.